Hypoxic-hypercapnic training-based correction of functional state of qualified athletes - Minina, E. N.; Safronova, N. S.; Lastovetsky, A. G.; Minin, V. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to substantiate the need for a differentiated approach to the correction of the functional state of qualified athletes using hypoxic-hypercapnic training.